The Influence of Entrepreneurship Attitudes and Interests on Learning Motivation and Its Implication on Student Professional Competency at Teacher Training and Education Faculty of Pasundan University - Setiani, Ani; Novendra, Afief Maula (European Journal of Social Science Education and Research, 2018)
The teachers’ roles which are needed in encountering the ASEAN Economic Community (MEA) are tough teachers, able to develop the knowledge, attitudes, and skills of learners. This study is aimed to find and examine the influence of entrepreneurship attitudes and interests on learning motivation and its implication to the students’ professional competence at Teacher Training and Education Faculty of Pasundan University, with 43 students as sample. The research method is analysis descriptive method by using path analysis. The results of this study are as follows: 1) The state of students’ entrepreneurship attitude is included in good category, with average score of 4.06; 2). The state of entrepreneurship interest is in good category, with average score of 4.17; 3) The state of learning motivation is in good category, with average score of 4.14; 4) The state of students’ professional competence is in good category, with average score of 3.94; 5) There is influence of entrepreneurship attitude (X1) to learning motivation (Y) with total influence of 32.8 percent, interest in entrepreneurship (X2) on learning motivation (Y) with total influence of 30.47 percent. There is influence of entrepreneurship attitude (X1), and entrepreneurship interest (X2), simultaneously to learning motivation (Y) with total influence of 63.3 percent; 6) There is influence of learning motivation (Y) to professional competence (Z) of 67.7 percent. With the hope lecturers are able to include the understanding of entrepreneurship spirit and mental in every learning, so that the students of teacher program have entrepreneurship spirit and mental in process of professional development through learning practice.